2013
DOI: 10.1088/0004-637x/767/2/118
|View full text |Cite
|
Sign up to set email alerts
|

The Prism Multi-Object Survey (Primus). Ii. Data Reduction and Redshift Fitting

Abstract: The PRIsm MUti-object Survey (PRIMUS) is a spectroscopic galaxy redshift survey to z ∼ 1 completed with a low-dispersion prism and slitmasks allowing for simultaneous observations of ∼ 2, 500 objects over 0.18 deg 2 . The final PRIMUS catalog includes ∼130,000 robust redshifts over 9.1deg 2 . In this paper, we summarize the PRIMUS observational strategy and present the data reduction details used to measure redshifts, redshift precision, and survey completeness. The survey motivation, observational techniques,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 15 publications
8
163
1
2
Order By: Relevance
“…In addition, we use photometric redshifts and their errors to et al 2013), 3D-HST (Skelton et al 2014;Momcheva et al 2016), FMOS-COSMOS (Silverman et al 2015), VVDS (Le Fèvre et al 2013), VIPERS PDR1 (Garilli et al 2014), SDSS DR12 (Alam et al 2015), WiggleZ DR1 (Drinkwater et al 2010), DEEP2 DR4 (Davis et al 2003;Newman et al 2013), and PRIMUS DR1 (Coil et al 2011;Cool et al 2013). …”
Section: Line Identificationmentioning
confidence: 99%
“…In addition, we use photometric redshifts and their errors to et al 2013), 3D-HST (Skelton et al 2014;Momcheva et al 2016), FMOS-COSMOS (Silverman et al 2015), VVDS (Le Fèvre et al 2013), VIPERS PDR1 (Garilli et al 2014), SDSS DR12 (Alam et al 2015), WiggleZ DR1 (Drinkwater et al 2010), DEEP2 DR4 (Davis et al 2003;Newman et al 2013), and PRIMUS DR1 (Coil et al 2011;Cool et al 2013). …”
Section: Line Identificationmentioning
confidence: 99%
“…W1 is also one of the areas selected by the PRIMUS survey (Cool et al 2013). Using only the PRIMUS reliable objects (PRIMUS flag 3 and 4), there are 2495 objects for which VIPERS measures a reliable redshift (flag 2 through 9) in VIPERS.…”
Section: P(x|y)mentioning
confidence: 99%
“…Using only the PRIMUS reliable objects (PRIMUS flag 3 and 4), there are 2495 objects for which VIPERS measures a reliable redshift (flag 2 through 9) in VIPERS. For this comparison, we consider two measurements to be concordant when Δ/(1 + z) < 3(σ 2 zVIPERS + σ 2 zPRIMUS ) 1/2 , where σ zPRIMUS = 0.003 for PRIMUS flag = 4 and σ zPRIMUS = 0.015 for PRIMUS flag = 3 (Cool et al 2013).…”
Section: P(x|y)mentioning
confidence: 99%
“…Silverman et al 2009;Rosario et al 2013). Aird et al (2012, hereafter A12) took a different approach, starting with a sample of galaxies out to z ∼ 1 (from the Prism Multi-object Survey: Coil et al 2011;Cool et al 2013) and determining the probability of finding an X-ray AGN within such galaxies as a function of the galaxy properties: stellar mass, redshift, and colour. A12 showed that the probability of hosting an AGN can be described by a power-law distribution of specific black hole accretion rates (hereafter, λsBHAR, the rate of black hole accretion normalised relative to the host stellar mass).…”
Section: Introductionmentioning
confidence: 99%